Summer Male Call Index Relative to Nesting Chronology and Autumn Density of the Northern Bobwhite - Theron M. Terhune; Richard G. Hamrick; D. Clay Sisson; H. Lee Stribling (National Quail Symposium Proceedings, 2017)
We studied breeding season male call counts and breeding behavior of the Northern Bobwhite (Colinus virginianus) to determine the relationship between male calling activity and nesting chronology. Additionally, we examined the relationship between breeding season call counts and fall population size. Standardized call count routes were conducted on 6 different sites located in southwest Georgia and north Florida during the breeding season months (1 Apr - 31 Sep) in 2001 and 2002. An information theoretic approach was used to evaluate a set of 7 candidate, linear-mixed models describing breeding season calling of bobwhite males. Of the candidate models, the model in which call counts depended on year and a quadratic effect of the number of incubating hens was the best approximating model, suggesting that the percentage of incubating hens had the greatest influence on activity of calling males. We also used multiple linear regression models to predict autumn northern bobwhite abundance from mean numbers of calling male bobwhites detected during the breeding season. Peaks in male calling activity occurring during June and July demonstrated a strong relationship (R2 = 0.987) with autumn population size, suggesting breeding season call counts were useful indices of autumn bobwhite abundance.
Keywords: Colinus virginianus; mortality; northern bobwhite; southeastern USA; survival; telemetry